2010
DOI: 10.1002/clen.200900155
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Impact of Ferti‐irrigation by Post‐methanated Distillery Effluent on Groundwater Quality

Abstract: The impact assessment of molasses‐based distillery‐effluent irrigation on groundwater quality around village Gajraula in the district of Jyotiba Phule Nagar, Uttar Pradesh, India was studied by sampling groundwater on monthly intervals consecutively for summer, winter and monsoon seasons during 2006–2007 and water quality parameters, viz. pH, electrical conductivity (EC), chloride (Cl−), sulphate (SO 42−), nitrate (NO 3−), chemical oxygen demand (COD), total solids (TS), total dissolved solids (TDS), sodium (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The other two wells revealed DO of 1.9 and 2.4 mg/l which, though still low, indicated an indirect impact of the landfill on them. Similar results were reported in Chauhan and Rai (2010) and Akinbile (2006) Table 3, most heavy metals tested for were not detected with the exception of iron, lead, zinc, and chromium which indicated the presence of toxic wastes coming perhaps from disposed off battery cells, used aerosol cans, and other materials with a certain degree of toxicity.…”
Section: Water Analysessupporting
confidence: 86%
See 1 more Smart Citation
“…The other two wells revealed DO of 1.9 and 2.4 mg/l which, though still low, indicated an indirect impact of the landfill on them. Similar results were reported in Chauhan and Rai (2010) and Akinbile (2006) Table 3, most heavy metals tested for were not detected with the exception of iron, lead, zinc, and chromium which indicated the presence of toxic wastes coming perhaps from disposed off battery cells, used aerosol cans, and other materials with a certain degree of toxicity.…”
Section: Water Analysessupporting
confidence: 86%
“…However, the presence of chromium (0.25 mg/l) in the sample at 100 metres distance from the landfill may suggest pollution from a nearby abattoir and not from the landfill site. Similar view is shared by Chauhan and Rai (2010).…”
Section: Water Analysesmentioning
confidence: 97%
“…In general, the values of HMC and other physico‐chemical characteristics in soil were highest in summer followed by winter and lowest in rainy season. This showed similarity with previous studies 14, 26. This might be due to dilution effect by excess precipitation in rainy season and concentration effect by evaporation during summer, as has been argued by Leung and Jiao 28.…”
Section: Resultssupporting
confidence: 92%
“…1). As the pH of water body is very important in influencing the solubility and toxicity of metals, these pH ranges were used to access the metal toxicity in the water resources under consideration 26. The effluents of both industries have heavy metals greater than the prescribed limit and hence call for treatment before discharge.…”
Section: Resultsmentioning
confidence: 99%
“…It has unearthed agricultural potential of certain effluent and their probable use as irrigation source during fresh water scarcity, which are otherwise reported to defile natural resources and degrading the health of natural ecosystem. (Chauhan and Rai, 2010) reported that reuse of wastewater comprises organic and inorganic constituents that could meet nutrients requirement of crops, improve soil fertility, decrease the fertilizer and manure requirement. Distilleries, one of the most important agro-based industries in India, produce ethyl alcohol from molasses for potable and industrial uses.…”
Section: Introductionmentioning
confidence: 99%